Versatile hermit crabs harness multiple-source energy from coastal mudflats: implications for fish production - Teoh, H.W.; Chong, V.C. (Kluwer (now part of Springer), 2015)
The versatile hermit crabs, Diogenes moosai and Diogenes lopochir, are hypothesised to utilise multiple primary sources of energy in the coastal mudflat. Stable carbon and nitrogen isotopes were analysed to determine the primary sources of nutrition (mangrove, benthic microalgae and phytoplankton) and trophic contribution of mudflat hermit crabs to fish predators in Matang mangrove estuary, Peninsular Malaysia. Stable isotope analysis in R showed that benthic microalgae are the major contributor of the total carbon assimilated by diogenid hermit crabs, followed by phytoplankton and mangrove. Interestingly, hermit crabs are one of the few marine organisms that can digest and assimilate lignocellulosic carbon of the mangrove. However, the relative contribution of the primary sources is site dependent and varies along the estuarine gradient with increasing dependency on mangrove-derived carbon by hermit crabs from offshore waters to estuary. The Sciaenidae is the major group of predatory fish of hermit crabs; the implication is that the dense population of hermit crabs with their versatile feeding habits channels energy from three basal sources to support coastal fish production.